PROGRAM POJOK BACA SEBAGAI STRATEGI GURU DALAM MEMOTIVASI MINAT BACA SISWA KELAS VIB DI SDN 17 DAUH PURI DENPASAR - Made Nadia Anjani Putri; I Nyoman Linggih; Ni Nyoman Ayu Suciartini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The reading interest of Grade VI B students at SDN 17 Dauh Puri Denpasar remains varied. Some students have developed reading habits, while others still require motivation and encouragement from teachers. To improve students' reading interest, the school implements a learning-page-based reading corner program by utilizing the school environment as a literacy medium. This study aims to describe the condition of students' reading interest, teachers' strategies in motivating reading interest through the learning-page-based reading corner program, and the impact of the program on the reading interest of Grade VI B students at SDN 17 Dauh Puri Denpasar. This study employed a qualitative approach with a descriptive research design. The theories used in this study include Constructivist Theory, Piaget’s Theory, and Vygotsky’s Theory. Data were collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. Data validity was tested using source triangulation and technique triangulation. The results of the study indicate that the learning-page-based reading corner program was implemented through three stages: planning, implementation, and evaluation. The program had a positive impact on increasing students' interest in reading, helping students gain knowledge and understand learning materials more easily, and becoming an effective alternative for motivating reading interest among elementary school students.